THE ROLE OF KNOWLEDGE MANAGEMENT TECHNOLOGIES IN THE DIGITAL TRANSFORMATION OF QUALITY MANAGEMENT SYSTEMS IN THE FOOD INDUSTRY - VYNNYCHUK, Roksolana; MAKOHIN, Petro; KOMAROVSKYI, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores the role of knowledge management technologies in the digital transformation of quality management systems in food industry enterprises. It substantiates that knowledge has become a key strategic resource ensuring competitiveness, innovativeness, and sustainability of production in the context of globalization and the digital economy. The study demonstrates that an effective quality management system cannot function without integrating knowledge-based technologies that form the foundation of corporate memory, promote staff learning, experience exchange, and support informed managerial decision-making. Based on the analysis of classical theoretical approaches (Nonaka, Davenport, Probst), the essence of knowledge management is defined as a continuous cycle of creating, sharing, and applying knowledge within the production environment. International standards ISO 9001:2015, HACCP, IFS, and BRC are considered as institutional frameworks that regulate the processes of formalizing, preserving, and exchanging organizational knowledge. The paper identifies the key tools of knowledge management, including ERP systems, CRM platforms, data warehouses, expert systems, and AI/ML technologies. It is proven that their implementation enhances process transparency, reduces error risks, and enables the creation of intelligent quality management systems (Quality 4.0). The experience of leading global companies such as Nestlé, Danone, Unilever, and Cargill, as well as Ukrainian enterprises such as MHP, Halychyna, and Kernel, is analyzed to demonstrate practical realization of knowledge-oriented digital strategies in production processes. The research highlights that the integration of digital technologies and systematic knowledge management forms a dynamic development ecosystem where information is transformed into knowledge, and knowledge – into strategic decisions. Future research directions include developing methodologies for assessing the efficiency of knowledge-based technologies and creating maturity models for evaluating the digital transformation level of food industry enterprises.